Satisfaction Study of Using Hearing Protection Device Among Sawmill Workers In Kuantan, Malaysia - Mainul, Haque; Nor Iza, A.Rahman; Siti Najihah, Yahya (2016)
The prevalence of Noise-Induced Hearing Loss is increasing worldwide. Major factors contribute to this situation is the breach of the preventive measures. This study aimed to identify factors that caused the industrial workers to ignore the usage of the hearing protection device (HPD). Semi-structured focus group discussion was conducted to the sawmill workers of Pahang, Malaysia. Purposive sampling method was performed to obtain participants, who was exposed to continuous noise, working in the industrial field and frequently or never used the HPD during working. Participants were differed in term of gender, age, working experience and job. The conducted focus group discussion was recorded and all related information was transcribed. Analysis of the theme for the study was conducted using QSR Nvivo 9.2. Three main themes were identified which are: uncomfortable, less awareness and barrier in communication. 58% of the workers reported on uncomfortable feeling while 42% were lack of awareness and 25% feel that the devices created a barrier in communication. Therefore, as uncomfortable feeling was the main cause of the industrial workers not to wear the HPD, new types of HPD that follows user requirement should be invented.